Risk factors for sleep disturbances and low quality of life in adolescents with epilepsy - Salendu, Praevilia Margareth; Manurung, Elsa Ameliana (Indonesian Pediatric Society, 2025)
Background Epilepsy impacts health-related quality of life and increases sleep disturbances. Duration of medication use, recurrent seizures, number of anti-epileptic drugs (AEDs), abnormal electroencephalography (EEG), and comorbidities are factors that might affect sleep and quality of life in adolescents with epilepsy. Objective To analyze risk factors related to sleep disturbances and quality of life in adolescents with epilepsy. Methods This analytical-observational study was performed in epilepsy outpatients treated between January – June 2024, of adolescent age, and had used AEDs for more than a year. Quality of life was evaluated using the Pediatric Quality of Life InventoryTM (PedsQLTM) – Epilepsy Module, and sleep disturbances were evaluated using the Sleeping Disturbance Scale for Children (SDSC) questionnaire. Fisher’s and Kolmogorov-Smirnov analyses were performed along with logistic regression for multivariate analysis. Results Forty-eight patients participated in this study. Subjects’ mean age was 12.69 (SD 2.4) years and 54.2% of subjects were male. Mean duration of medication use was 2 years with the minimum interval of the last seizure episode occurring 1 week before observation. More than half of the patients (60.4%) had abnormal EEGs. Most patients were treated with monotherapy AED (81.3%). Seventy five percent of patients had low quality of life and 47.9% had sleep disturbances. In multivariate analysis, adolescents with abnormal initial diagnosis EEGs had 19.1 times higher risk of sleep disturbances (95%CI 3.3 to 110.4 P= 0.001) than those with normal EEGs. Among patients with abnormal EEGs, sleep disturbances increase the risk of low quality of life (OR 1.6; 95%CI 0.93 to 2.73; P=0.015) . Conclusion Abnormal EEG was a significant risk factor for sleep disturbances and low quality of life in adolescent epilepsy patients.